DEVELOPMENT OF CANVA-BASED INTERACTIVE LEARNING MEDIA IN CLASS VIII SCIENCE SUBJECTS HUMAN BLOOD CIRCULATION SYSTEM - Kusmaniar; Siti Mayang Sari; Akmaluddin; Mardhatillah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
IPA is a science group that explains natural phenomena, living things, systems in the body which are rather difficult to understand without using interactive media. The circulatory system in humans is one of the interesting subject matter for science class VIII which is interesting but difficult for students to understand because it involves the internal mechanisms that exist in the human body. One of the supporting factors in efforts to increase students' understanding of the material being taught is to use appropriate media and in accordance with the subject matter being taught. This research was conducted at SMPN 2 Sawang. The ultimate goal of this research is to produce Canva-based interactive learning media. The research method used is descriptive qualitative with qualitative and quantitative data analysis, data collection techniques by interviews, questionnaires and observation. The development of Canva-based interactive media uses the 3 stages of the IDI model, namely define is carried out by distributing questionnaires and interviews with students and educators to get a complete picture of the situation in the field. the develop stage is designing interactive learning media based on Canva using then validation by experts (validators), and the evaluation stage aims to find out the benefits, convenience, and time efficiency of using media by teachers and students. The validity value is 95.2% with very feasible criteria, practicality by the teacher is 95.8% with very feasible criteria and 97.19% students with very feasible criteria. The results of the study show that Canva-based learning media is valid and practical for learning